COVID-19 and Labour Law: Norway - Mulder, Bernard Johann (Italian Labour Law e-Journal, 2020)
The Norwegian Government has in March announced immediate measures to avoid unnecessary layoffs and bankruptcies in viable companies from the shock of corona virus and Covid-19 pandemic. It has therefor responded to the situation with different measures, from closing down schools to financially support businesses and employees.